PROFIL KEHIDUPAN REMAJA MANUSIA SILVER DI PRUMPUNG SAWAH, JAKARTA TIMUR - Lebang Pakan, Marcelina Sanda (Istek Widuri Jakarta, 2023)
This study discusses the Life Profile of Silver Human Adolescents in Prumpung Sawah, East Jakarta. The method used in this research is qualitative which describes or describes the data obtained from the field with a qualitative approach. The selection of informants used purposive sampling and tested the validity of the data using a triangulation technique. The results of this study are the profile of the life of silver human adolescents, in general, they are young boys aged 14-17 years, dropping out of school due to not being able to pay school fees, divorced parents, broken homes, low education, family economic difficulties, parents who do not have a permanent job, have an income of only IDR 100-200,000, and live in a small rented house. Meanwhile the need to pay for electricity, pay for rent, is not enough to meet their needs so they work as human beings silver.